A numerical-experimental dynamic analysis of high-efficiency and broadband bistable energy harvester with self-decreasing potential barrier effect. (1st July 2022) - Chen, Lin; Liao, Xin; Sun, Beibei; Zhang, Ning; Wu, Jianwei
Highlights: A novel bistable energy harvester with a self-decreasing potential barrier effect (BEH-DB) is proposed. The nonlinear dynamic characteristics such as bifurcations, inter-well harmonic and subharmonic 1/3 orbits, and chaotic motion are investigated. The maximum average power generated by the BEH-DB is approximately 9.02 mW. The effective bandwidth of the BEH-DB is approximately 16.17 Hz. Abstract: It is difficult for a conventional bistable energy harvester (CBEH) to form inter-well motion under a weak excitation, resulting in a narrow output bandwidth. In this paper, a bistable energy harvester with a self-decreasing potential barrier effect (BEH-DB) is proposed. It adopts a spring-magnetic oscillator to rectify the cantilever beam bi-directionally causing the potential barrier to be dynamically lowered when returning to the trivial position; while the potential energy is enhanced when moving away from the trivial position. The theoretical model is established by using Euler-Bernoulli's stepped beam and magnetic dipole theories. The influence of system parameters on the performance of the self-decreasing potential barrier is studied by tracking the trajectories on the potential energy surface. The frequency and amplitude sweeps, phase portraits, Poincare maps, and bifurcation analysis are used numerically to investigate the dynamics of the system. The simulation results present a series of complex dynamic behaviors such as intra-well, inter-well harmonic and sub-harmonic orbits, and chaotic motion. The BEH-DB is more easily to be excited to the inter-well orbit to form a large oscillation in an ultra-wide bandwidth, even at the low frequency. Its effective bandwidth and maximum average power are approximately 16.17 Hz and 9.02mW, respectively. Finally, the experiment was carried out, which illustrates that the power generation capacity and bandwidth of the BEH-DB are improved several times that of the CBEH. The experimental results are agreed qualitatively with the numerical simulation. The proposed BEH-DB can be used to harvest energy efficiently and broadly from a low or ultra-low frequency ambient vibration.